I mercati coperti di Giuseppe Mengoni Architettura, ingegneria e urbanistica per Firenze Capitale - PANATTONI, RITA (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Florence, the new capital of the Kingdom of Italy (1864-1870), went through a period of great transformation, which would leave significant traces in the city's image and structure. The construction of the new markets is emblematic of the city's infrastructural modernisation, with the introduction of new architectural languages and construction technologies of international standing. The Central Market at San Lorenzo is one of the most representative buildings of this modernisation process, a true masterpiece by Giuseppe Mengoni, the renowned designer of the Galleria Vittorio Emanuele II in Milan. This volume reconstructs its history from a comparative and interdisciplinary perspective, based on largely unpublished documentation. It places Florence and its new market in a European context where architecture, town planning, politics and finance are tightly intertwined. The Florentine case becomes a paradigm of the renewal of Italian architecture in the second half of the 19th century.